Pemenuhan Kebutuhan Tokoh Utama dalam Novel 7 Prajurit Bapak Karya Wulan Nuramalia - Lestari, Yuliana Sukma; Israhayu, Eko Sri (CV. Eduartpia Publisher, 2023)
This research has the purpose to describe the fulfilling the needs of the main character in the novel 7 Prajurit Bapak by Wulan Nuramalia which uses Abraham Maslow's humanistic personality theory. This type of research uses descriptive qualitative research methods with a literary psychology approach. The data in this study are in the form of words, sentences, phrases or paragraphs that have something to do with fulfilling the needs of Abraham Maslow's humanistic personality theory. The findings obtained in this study are that the main character can fulfill the needs in the form of physiological needs, belonging and love needs, self-esteem needs, and self-actualization needs. However, there is one need that the main character cannot fulfill, namely the safety needs. Keywords: Humanistic Abraham Maslow, 7 Prajurit Bapak, Hierarchy of Needs